Growth performance, physiological response, and tissue microarchitecture of the carp Labeo rohita challenged with AFB1 are improved by supplementing with turmeric - Bhatt, Deepa; Holeyappa, Shanthanagouda A.; Pandey, Abhed; Bansal, Neelam; Hundal , Jaspal S.; Khairnar , Sachin O. (Spanish Journal of Agricultural Research, 2024)
Aim of study: To examine the impact of dietary supplementation with turmeric (TM) (Curcuma longa) on growth, haematological, biochemical parameters, and histoarchitecture in rohu (Labeo rohita) challenged with aflatoxin B1 (AFB1).Area of study: Ludhiana, Punjab, India.Material and methods: A completely randomized design involved the utilization of 225 fingerlings distributed across five treatments with three replicates each. Diets were allocated as follows: T1 denoted the negative control diet, T2 comprised AF100, while T3, T4, and T5 were formulated with AF25TM, AF50TM, and AF100TM, respectively.Main results: The results indicated a negative correlation between AFB1 dosage in feed and fish growth, with higher doses resulting in decreased growth. Significant changes were observed in haematological parameters, including reductions in total erythrocyte count, total leukocyte count, haemoglobin, and packed cell volume, alongside alterations in biochemical parameters, such as decreases in total protein, albumin, and globulin levels, and an increase in glucose levels and albumin/globulin ratio. Additionally, elevated levels of aspartate aminotransferase, alanine aminotransferase, catalase and superoxide dismutase were noted in T2 and T5 compared to other treatments. AFB1 exposure also led to damage in the microarchitecture of the brain, kidney, and liver tissues, although inclusion of TM at 25 ppb AFB1 showed signs of recovery.Research highlights: The changes observed were dose-dependent, and supplementation of TM showed increased resistance against AFB1 and the greatest improvement in T3. Therefore, a diet containing 5 g TM kg-1 would lower AFB1 contamination of 25 ppb compared to 50 and 100 ppb. In conclusion, supplementing TM in fish feeds can help regulating the AFB1, which in turn can improve sustenance-based output.